2006
DOI: 10.1074/jbc.m511319200
|View full text |Cite
|
Sign up to set email alerts
|

Internal Ribosome Entry Site-mediated Translation of Apaf-1, but Not XIAP, Is Regulated during UV-induced Cell Death

Abstract: Components of the cellular translation machinery are targets of caspase-mediated cleavage during apoptosis that correlates with the inhibition of protein synthesis, which accompanies apoptosis. Paradoxically, protein synthesis is required for apoptosis to occur in many experimental settings. Previous studies showed that two proteins that regulate apoptosis by controlling caspase activity, XIAP and Apaf-1, are translated by a unique, cap-independent mechanism mediated by an internal ribosome entry site (IRES) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
(56 reference statements)
0
30
0
Order By: Relevance
“…We next investigated the involvement of hnRNP A1 in apaf-1 mRNA translation, because apaf-1 IRES-mediated translation is activated after UVC irradiation in human embryonic kidney (293T) cells (Ungureanu et al, 2006) and hnRNP A1 is redistributed to the cytoplasm after UVC irradiation ( Figure 5A; as expected from van der Houven van Oordt et al, 2000). To first confirm the effect of UVC irradiation on endogenous apaf-1 mRNA translation, we examined the polysomal association of this mRNA in 293T cells.…”
Section: Cytoplasmic-relocalized Hnrnp A1 Inhibits Apaf-1 Ires-mediatmentioning
confidence: 90%
See 2 more Smart Citations
“…We next investigated the involvement of hnRNP A1 in apaf-1 mRNA translation, because apaf-1 IRES-mediated translation is activated after UVC irradiation in human embryonic kidney (293T) cells (Ungureanu et al, 2006) and hnRNP A1 is redistributed to the cytoplasm after UVC irradiation ( Figure 5A; as expected from van der Houven van Oordt et al, 2000). To first confirm the effect of UVC irradiation on endogenous apaf-1 mRNA translation, we examined the polysomal association of this mRNA in 293T cells.…”
Section: Cytoplasmic-relocalized Hnrnp A1 Inhibits Apaf-1 Ires-mediatmentioning
confidence: 90%
“…To first confirm the effect of UVC irradiation on endogenous apaf-1 mRNA translation, we examined the polysomal association of this mRNA in 293T cells. Polysome gradients were prepared from untreated cells or cells irradiated with a UVC dose of 300J/m 2 , a dose previously shown to induce 50% cell death (Ungureanu et al, 2006). UVC irradiation caused a large decrease in polysomal mRNAs and a corresponding increase in free ribosomes and ribosomal subunits, reflecting a global reduction in translation initiation efficiency ( Figure 5B).…”
Section: Cytoplasmic-relocalized Hnrnp A1 Inhibits Apaf-1 Ires-mediatmentioning
confidence: 97%
See 1 more Smart Citation
“…We have earlier reported that UVR results in an inhibition of global protein synthesis, whereas simultaneously enhancing translation of the proapoptotic protein Apaf-1 through an IRES-dependent mode of translation. 14 In the course of these experiments we observed that the levels of the anti-apoptotic gene cIAP1 were significantly reduced following UVR (Figure 1a). We wished to determine if this reduction in cIAP1 levels is because of changes in protein or mRNA stability.…”
Section: Resultsmentioning
confidence: 87%
“…37 Previous work showed that exposure of cells to UVR results in an inhibition of global protein synthesis. 14,38,39 This observation leads to the question of why an additional regulatory mechanism, such as degradation of cIAP1 mRNA, would be employed by cells to silence the expression of target genes following UVR. It is interesting to note that several genes involved in the regulation of cell proliferation and survival are translated by an IRES-dependent mode of translation that escapes some of the control steps that govern global, cap-dependent translation.…”
Section: Discussionmentioning
confidence: 99%